Thermal Analysis and Crystallization of MY(Sb70Te30)100-Y (M = Ag, Sn; Y = 0, 7.5) Amorphous Thin Films - Rocca, Javier Alejandro (2023)
Antimony-telluride based phase-change materials doped with different metals have been proposed to be ideal materials for improving the performance of phase-change memories. It is well known that Sb70Te30 thin films show a sharp fall in the electrical resistance in a narrow temperature range when heating. Therefore, it is interesting to study the effect of adding metallic atoms into this composition. In this work, the crystallization of My(Sb0.70Te0.30)100-y (M = Ag, Sn; y = 0, 7.5) amorphous thin films, obtained by pulsed laser deposition, has been studied by means of differential scanning calorimetry under continuous heating regime. The as-deposited samples and the crystallization products have been characterized by X-ray diffraction. The crystallization and melting temperatures were determined, as well as the enthalpies involved in such processes. The activation energy for crystallization was also determined. From the obtained results, it is observed that the addition of metals shifts the crystallization process to higher temperatures around 15-25 K and increases its activation energy. The transformation diagrams (Temperature-Time-Transformation and Temperature-Heating rate-Transformation) are calculated. The experimental results are discussed and correlated with proposed structures for the glass and the crystalline states. The present results are also compared with those reported by other authors.